2015
DOI: 10.7306/gq.1241
|View full text |Cite
|
Sign up to set email alerts
|

The use of gadolinium and europium concentrations as contaminant tracers in the Nida River watershed in south-central Poland

Abstract: 1 Jan Kochanowski Uni ver sity, Fac ulty of Math e mat ics and Nat u ral Sci ences, OEwiêtokrzyska 15G, 25-406 Kielce, Po land Migaszewski, Z.M., Ga³uszka, A., 2016. The use of gad o lin ium and eu ro pium con cen tra tions as con tam i nant trac ers in the Nida River wa ter shed in south-cen tral Po land. Geo log i cal Quar terly, 60 (1): 67-76, doi: 10.7306/gq.1241 This pa per pres ents the re sults of rare earth el e ment (REE) de ter mi na tions in the Nowiny wastewater treat ment plant (NWWTP) effluent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Gadolinium chelates are widely used as contrasting agent in magnetic resonance imaging (MRI) medical exams, due to the high magnetic moment of the paramagnetic Gd 3+ ion (e.g., Kümmerer and Helmers, 2000;Migaszewski and Gałuszka, 2016;Möller et al, 2003). Since some Gdbased contrast agents are stable complexes and are not metabolized, after application they are excreted from the human body through urine and released to waste water treatment plants (WWTPs) and from here to aquatic environments almost unchanged (Knappe et al, 2005;Migaszewski and Gałuszka, 2016;Möller et al, 2000). Kümmerer and Helmers (2000) reported that the level of Gd in urine may reach 350 mg/L daily after the patient medical exam and 7 mg/L after 39 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gadolinium chelates are widely used as contrasting agent in magnetic resonance imaging (MRI) medical exams, due to the high magnetic moment of the paramagnetic Gd 3+ ion (e.g., Kümmerer and Helmers, 2000;Migaszewski and Gałuszka, 2016;Möller et al, 2003). Since some Gdbased contrast agents are stable complexes and are not metabolized, after application they are excreted from the human body through urine and released to waste water treatment plants (WWTPs) and from here to aquatic environments almost unchanged (Knappe et al, 2005;Migaszewski and Gałuszka, 2016;Möller et al, 2000). Kümmerer and Helmers (2000) reported that the level of Gd in urine may reach 350 mg/L daily after the patient medical exam and 7 mg/L after 39 days.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of the increasingly exploitation and application of this element, Gd has been detected in a wide diversity of ecosystems (Migaszewski and Gałuszka, 2016;Rogowska et al, 2018) being recognized as an emergent micropollutant in aquatic environments (Rogowska et al, 2018). It has been reported Gd concentrations with natural background levels of 1-4 ng/L to values up to 200-1100 µg/L at…”
Section: Introductionmentioning
confidence: 99%
“…The REEs have found an application in fingerprinting geologic and anthropogenic sources and in investigating geochemical processes that lead to fractionation of this element group in various environmental compartments, but particularly in surface and underground waters (e.g., Johannesson and Lyons 1995; Verplanck et al 2004; Bozau et al 2004; Gammons et al 2005; Knappe et al 2005; Leybourne and Johannesson 2008; Kulaksiz and Bau 2011; Migaszewski and Gałuszka 2015, 2016). In the surface water systems, the REE undergo fractionation between colloid/suspended matter and dissolved fractions (Ingri et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the anomaly of Eu due to naturally-occurring Eu were often observed in the samples from the upstream river water to estuarine water. 113…”
Section: Analytical Sciencesmentioning
confidence: 99%